2003
DOI: 10.1093/jac/dkg378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pharmacodynamics of meropenem in healthy volunteers following administration by intermittent infusion or bolus injection

Abstract: We conclude that a 3 h infusion of 0.5 g or 1 g of meropenem both give greater values for t > MIC than a 1 g bolus and that intermittent infusion may be a useful mode of administration in tropical countries where drug instability may prevent the use of continuous infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
4
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 11 publications
2
41
4
4
Order By: Relevance
“…As a consequence of these alterations in V and CL, the half-life (t 1/2 ) of antimicrobial agents can be affected, leading to undesirable therapeutic outcomes. In the current study, alterations of the PK of meropenem were found in comparison with an earlier study with healthy volunteers (17). The V of meropenem was greater and the CL of meropenem was lower than the values obtained from the previous study with healthy volunteers (17), resulting in Ͼ2-fold prolongation of the t 1/2 of this agent.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…As a consequence of these alterations in V and CL, the half-life (t 1/2 ) of antimicrobial agents can be affected, leading to undesirable therapeutic outcomes. In the current study, alterations of the PK of meropenem were found in comparison with an earlier study with healthy volunteers (17). The V of meropenem was greater and the CL of meropenem was lower than the values obtained from the previous study with healthy volunteers (17), resulting in Ͼ2-fold prolongation of the t 1/2 of this agent.…”
Section: Discussioncontrasting
confidence: 58%
“…In the current study, alterations of the PK of meropenem were found in comparison with an earlier study with healthy volunteers (17). The V of meropenem was greater and the CL of meropenem was lower than the values obtained from the previous study with healthy volunteers (17), resulting in Ͼ2-fold prolongation of the t 1/2 of this agent. A possible explanation for the PK changes in this study is that the study was undertaken with seriously ill patients with life-threatening infections and more than one-half of the recruited patients were experiencing renal dysfunction, as defined by MDRD CL Cr values of Յ60 ml/min.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, the mortality in animals infected with Streptococcus pneumoniae and treated with ␤-lactams is very low when levels of antibiotics exceed the MIC for 40 to 50% of the dosing interval (4). A previous study of healthy volunteers revealed that a 3-h infusion of 1 g of meropenem can maintain serum drug concentrations above the MIC for most pathogens in patients for 60% of an 8-h dosing interval (8). Thus, a 3-h infusion has been proposed as an appropriate mode of administration in tropical countries.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum plasma concentration (C max ) and the minimum plasma concentration (C min ) were determined by visual inspection of the individual plasma concentration-time profiles. From the individually fitted concentration-time curves, the TϾMICs were calculated for MICs of 16,8,4, and 1 g/ml. Results were expressed as mean values Ϯ standard deviations, and statistical comparisons were made using the Wilcoxon signedrank test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation